Design of the front-end system for a subexawatt laser of the XCELS facility. (September 2021) - Mukhin, I.B.; Soloviev, A.A.; Perevezentsev, E.A.; Shaykin, A.A.; Ginzburg, V.N.; Kuzmin, I.V.; Mart'yanov, M.A.; Shaikin, I.A.; Kuzmin, A.A.; Mironov, S.Yu.; Yakovlev, I.V.; Khazanov, E.A.
Abstract: A concept of the front-end system of the XCELS (eXawatt Center for Extreme Light Studies) facility is presented. Its design is aimed at achieving high stability of laser radiation parameters and possibility of their control in a wide range. Optically synchronised chirped signal (wavelength 910 nm, bandwidth more than 100 nm, and duration ∼3 ns) and pump (wavelength 1054 nm, bandwidth ∼1 nm, and duration ∼4 ns) pulses for XCELS parametric amplifiers will be implemented at the output of the front-end system. Chirped femtosecond pulses with energies above 100 mJ [no more than 15 fs long after compression, with carrier-envelope phase (CEP) stabilisation] will have a repetition rate up to 100 Hz, which will allow one to implement active energy stabilisation and to minimise the angular jitter of the emitted beam at the XCELS output. The application of picosecond pumping in the parametric amplifier of the front-end system should provide a high contrast of femtosecond pulses. The pump pulse will be linearly frequency-modulated; this approach will not affect the parametric amplification efficiency but make it possible to use spectral methods to control the pump pulse shape in order to form a pulse of specified shape at the output of power amplifiers, even under conditions of their strong saturation.